Chicken DDX3X Activates IFN-β via the chSTING-chIRF7-IFN-β Signaling Axis - Niu, Qiaona; Cheng, Yuqiang; Wang, Hengan; Yan, Yaxian; Sun, Jianhe (Frontiers in Immunology, 2019)
Asp-Glu-Ala-Asp (DEAD)-box polypeptide 3 X-linked (DDX3X) is an ATP-dependent RNA helicase, In addition to involvement of eukaryotic gene expression regulation, mammalian DDX3X has recently been found to regulate IFN-β production via the adaptor MAVS mediated cascade signaling. In our studies, we demonstrated that chicken DDX3X (chDDX3X) is also involved in the IFN-β regulation, and demonstrated that chDDX3X regulated IFN-β via an essential adaptor chicken stimulator of IFN genes (chSTING). We found that chDDX3X overexpression in DF-1 cells induced expression of IFN-β and inhibited avian influenza virus (AIV) or Newcastle disease virus (NDV) replication. Knockdown of chDDX3X decreased the production of IFN-β induced by RNA analog polyinosinic-polycytidylic acid and increased viral yield. Furthermore, chDDX3X was identified as a potential chSTING-interacting protein by co-immunoprecipitation (Co-IP) and liquid chromatography-tandem mass spectrometry (LC-MS/MS). And exogenous Co-IP in transfected cells with or without virus-stimulations further confirmed the interaction between chDDX3X and chSTING. With the gene overexpression and RNA interference studies, the chDDX3X was confirmed to be located upstream of chSTING and activate IFN-β via the chSTING-chTBK1-chIRF7-IFN-β signaling axis. In brief, our results suggest that chDDX3X is an important IFN-β mediator and is involved in RNA- and RNA virus-mediated chDDX3X-chSTING-IFN-β signaling pathway.